Uncertainty, Social Location and Influence in Decision Making: A Sociometric Analysis - Tushman, Michael L.; Romanelli, Elaine (Management Science, 1983)
This research investigates the relative impacts of formal status and informal communication roles on influence in administrative and technical decision making. While external information enters the organization via boundary spanning individuals, the exercise of influence at lower levels of the organization is dependent on mediating critical organizational contingencies. As the locus of task uncertainty shifts, so too does the relative influence of boundary spanning individuals and internal stars; the greater the task and environmental uncertainty, the greater the influence of boundary spanning individuals. Senior management are influential across task areas. The formal hierarchy and informal social processes complement each other in the exercise of influence. These results extend research which indicates that different information processing requirements require systematically different organizational processes to attend to that uncertainty.